ANALISIS MANAJEMEN RISIKO PADA HOME INDUSTRI UD. SAFNUR DESA LENGKONG KECAMATAN RAKIT KABUPATEN BANJARNEGARA - Solekan, Muhamad; Pujiyanto, Muhammad Aris; Sarno; Kinding, Dwi Putriana Nuramanah (Perwira Journal of Economics & Business, 2024)
UD. Safnur, a home industry in Banjarnegara Regency, focuses on agro-industry using local soybean products. Effective risk management is essential, especially in uncertain times, as home industries contribute significantly to the local economy. This study aims to identify the risk management process, assess potential risks, and analyze strategies to manage these risks. This study involves preparation, data collection, processing, analysis, and conclusion. The study was conducted in June 2024. The risk management process includes three stages: Risk Identification with SWOT analysis, Risk Assessment using a risk matrix, and Risk Response Plan Development. This study identified three main risk factors: Supply Risk, Operational Risk, and Marketing Risk. In the risk assessment, marketing risk is classified as high (red zone), while supply and operational risks are classified as low (yellow zone). Recommended risk responses include basic digital marketing training, offering promotions and discounts, product diversification, establishing partnerships with cooperatives and raw material suppliers, adopting financial technology, and using continuous band sealers. This study shows that by systematically identifying and assessing risks, and developing appropriate risk response strategies, UD. Safnur can manage the risks it faces effectively, so that it can contribute more significantly to the local economy in Banjarnegara Regency